Determination of Hg in water by CVAAS using 2-aminothiazole modified silica - Silva, Fábio Arlindo; de Alcântara, Ilton Luiz; Roldan, Paulo dos Santos; Padilha, Cilene do Carmo Federici; de Araújo, Adriana Barbosa; Valente, José Pedro Serra; Florentino, Ariovaldo de Oliveira; Padilha, Pedro Magalhães (Eclética Química, 2005)
This paper discusses a rapid and sensitive method developed to determine trace levels of mercury in natural water samples by cold vapor atomic absorption spectrometry using a preconcentration system composed by mini-column packed with 100 mg of 2-aminothiazol modified silica gel (SiAT) coupled on-line with the spectrometer’s cold vapor generator system. The optimum preconcentration conditions are also described here. The preconcentrated Hg(II) ions were eluted directly from the column to the spectrometer’s cold vapor generator system using 100 μL of 2 mol L -1 hydrochloric acid and the retention efficiency achieved exceeded 95%. The enrichment factors determined were 29, 38 and 46 using 3, 4 and 5 mL of preconcentrated aqueous solutions containing 400 ng L -1 of Hg. The detection limit calculated was 5 ng L -1 . The preconcentration procedure was applied to determine trace level mercury in spiked river water samples.